2015
DOI: 10.16943/ptinsa/2015/v81i4/48304
|View full text |Cite
|
Sign up to set email alerts
|

Simulation, Modelling and Design of Hydrogen Storage Materials

Abstract: In the current renewable energy scenario, one of the thrust areas is hydrogen generation and storage in an environmentfriendly and cost-effective fashion. The primary challenge of efficient generation as well as storage of hydrogen has triggered R&D all over the world. Various routes such as solar photovoltaic, solar thermal, nuclear and bio-inspired routes are being vigorously pursued; the costs are still rather high for the hydrogen economy to be viable for renewable energy. There has been a concerted effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, the efficient production, storage, and transportation of hydrogen are to be achieved for hydrogen-based economy. Among them, the storage of hydrogen has recently posed a great challenge to the scientific community, due to the difficulty in achieving a safe and efficient storage system which could store large amounts of hydrogen in a container of small volume, light weight, and low cost 1 2 3 4 5 6 7 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficient production, storage, and transportation of hydrogen are to be achieved for hydrogen-based economy. Among them, the storage of hydrogen has recently posed a great challenge to the scientific community, due to the difficulty in achieving a safe and efficient storage system which could store large amounts of hydrogen in a container of small volume, light weight, and low cost 1 2 3 4 5 6 7 8 .…”
mentioning
confidence: 99%
“…In 2015, the United States Department of Energy (USDOE) set the 2020 target of 5.5 wt% and the ultimate target of 7.5 wt% for the gravimetric storage capacities of onboard hydrogen storage materials for light-duty vehicles 8 . As of now, there have been several methods for storing hydrogen, such as physical storage methods where hydrogen is stored in vessels at very high pressures (e.g., 350 to 700 bar), cryogenic methods where hydrogen is stored at very low temperatures (e.g., 20 K), chemical storage in the form of metal hydrides, and adsorption-based storage in high surface area materials 1 2 3 4 5 6 7 . Experimentally, none of these methods has achieved the gravimetric and volumetric storage capacities set by the USDOE with fast kinetics, while some theoretical studies have reported materials with the ideal storage capacities.…”
mentioning
confidence: 99%
“…One of the distinctive qualities of hydrogen is that it produces a high energy per unit mass (120 MJ/kg) without releasing any pollutant by-products. 2,3 Despite these benefits, however, the use of hydrogen in practice is limited due to the obstacle of finding the most appropriate and affordable way to store and deliver hydrogen under normal environmental conditions. As per the criteria proposed by the United State Department of Energy (DOE-US), an effective hydrogen storage material should have a minimum storage capacity of up to 5.5 wt% by the year 2025 at moderate thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“… 1,2 Therefore, global associations like the US Department of Energy (US‐DOE) and the United Nations Environment Program (UNEP) have been encouraging the use of alternative clean and cost‐effective energy resources. To meet the global energy requirements, hydrogen is proposed to be one of the ideal sustainable alternative resources because of its natural abundance, higher mass‐specific energy (120 MJ/Kg) than the traditional fossil fuels (44 MJ/Kg) and non‐polluting nature 3,4 . But storage and distribution of hydrogen fuel under ambient circumstances have been major challenges for their commercial operations 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…To meet the global energy requirements, hydrogen is proposed to be one of the ideal sustainable alternative resources because of its natural abundance, higher mass-specific energy (120 MJ/Kg) than the traditional fossil fuels (44 MJ/Kg) and non-polluting nature. 3,4 But storage and distribution of hydrogen fuel under ambient circumstances have been major challenges for their commercial operations. 5,6 The US-DOE has set a benchmark goal of 5.5 wt% gravimetric density for reversible hydrogen storage by the year 2025 within the temperature range of 300 to 400 K and pressure range of 3 to100 bar.…”
Section: Introductionmentioning
confidence: 99%